Elevated systemic immune-inflammation index is associated with stroke-associated pneumonia in acute ischemic stroke: a retrospective cohort study - Duan, Tingting; Yang, Ming; Zhang, Yiming; Zhu, Chunyan; Rao, Zichen (Frontiers in Neurology, 2025)
Stroke-associated pneumonia (SAP) is a frequent complication of acute ischemic stroke (AIS) that contributes to poor clinical outcomes. The systemic immune-inflammation index (SII), derived from neutrophil, lymphocyte, and platelet counts, may reflect post-stroke immune imbalance, but its role in predicting SAP remains unclear. In this retrospective study, we analyzed 1,767 AIS patients and evaluated the association between log₂-transformed SII and the occurrence of SAP using multivariable logistic regression, generalized additive models, and two-piecewise regression. SAP developed in 21.3% of patients during hospitalization. Higher SII levels were independently associated with increased SAP risk after adjustment for age, sex, vascular risk factors, comorbidities, baseline National Institutes of Health Stroke Scale (NIHSS) score, and dysphagia assessed by Kubota Water Drinking Test (KWDT). Patients in the highest SII quartile had a significantly greater likelihood of developing SAP compared to those in the lowest quartile (adjusted odds ratio = 2.03, 95% confidence interval: 1.21–3.38, p = 0.0069). A non-linear, threshold-dependent relationship was identified, with SAP risk increasing substantially beyond log₂-SII ≈ 8.5. Receiver operating characteristic (ROC) analysis demonstrated moderate predictive performance of SII for SAP (area under the curve (AUC) = 0.726), while C-reactive protein (CRP) showed superior discrimination (AUC = 0.826 p < 0.0001). Supplementary sensitivity analyses, including a fully adjusted model without NIHSS and KWDT and an alternative model replacing these with the A2DS2 score (Age, Atrial fibrillation, Dysphagia, Sex, Stroke Severity), showed consistent results, supporting the robustness of our findings. These findings suggest that SII may serve as a cost-effective and accessible biomarker to aid early identification of high-risk AIS patients.